Основні парадигми аналізу "консенсусу" в західній науці - Карагіоз, Р. С.; Карагиоз, Р. С.; Karagioz, R. (My University, 2012)
In the article basic theoretical interpretations of understanding of social and political essence of consensus, most popular in western political science are examined.
Карагіоз Р. С. Основні парадигми аналізу "консенсусу" в західній науці / Р. С.Карагіоз // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 46. – С. 66-74.
Keywords: суспільно-політична сутність консенсусу; західна політична наука; консенсус у західній політичній науці; общественно-политическая сущность консенсуса; западная политическая наука; консенсус в западной политической науке; socio-political nature of consensus; Western political science; the consensus in the western political science